Lodo de indústria têxtil e água residuária de suinocultura na produção de mudas de eucalipto - Pelissari, Rodrigo Augusto Zembrzuski (2007)
The objective of this work was to evaluate the effects of textile silt, seasoning and irrigation with wastwater from swineactivities on the production of Eucalyptus grandis W, Hill ex Maiden. The treatments were constituted by three factor: quimical season (0, 1 and 2 grams of NPK 14-14 by tube), irrigation (water and remaining wastewater from swine) and substratum with five levels of fraction of the textile silt and commercial substratum (0, 25, 50, 75 and 100%). Four periods was evaluated during the production (germination, 21 days), (50% shadowning, 40 days), (18% shadowning, 20 days) and (full sun, 9 days) with a total of 90 days of production. The irrigation was performed by aspersion, with 12 mm/day. The agronomic parameters evaluated were hight (H), diameter (D) and the relation hight/diameter (H/D) of the plants. The experimental delineation used was entirely casual on factorial project with 39 repetitions per treatment. The results obtained allowed to conclude that, the quimical season propitiated effect on the plants hights on the last periods of production. The substratum factor presented it self on the negative form when used in 100% of the textile silt. The wastewater from presented the best results for the samples at diameter and at hight. Using the parameter of the Hight/Diameter relation to evaluation of the samples, the remaining wastewater propitiated a anticipation of 30 days on the production of the eucalyptus.